2015
DOI: 10.1103/physrevapplied.4.064012
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion of Bubble-Based Acoustic Microswimmers

Abstract: Acoustic microswimmers present great potential for microuidic applications and targeted drug delivery. Here we introduce armoured microbubbles (size range, 10 − 20 µm) made by threedimensional microfabrication which allows the bubbles to last for hours even under forced oscillations. The acoustic resonance of the armoured microbubbles is found to be dictated by capillary forces and not by gas volume, and its measurements agree with a theoretical calculation. We further measure experimentally and predict theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 31 publications
1
118
0
Order By: Relevance
“…For other applications, such as the removal of biofilms, with typical elastic modulus of 10 2 Pa and shear strength of approximately 10 Pa (Flemming, Wingender & Szewzyk 2011), it is desirable to achieve a more steady and controlled flow, even if this implies a substantially lower shear rate (Verhaagen 2012;. Such acoustic streaming flow induced by an oscillating bubble has been also used to propel microparticles (Bertin et al 2015) or even milimetric objects (Dijkink et al 2006).…”
Section: R Bolaños-jiménez and Othersmentioning
confidence: 99%
“…For other applications, such as the removal of biofilms, with typical elastic modulus of 10 2 Pa and shear strength of approximately 10 Pa (Flemming, Wingender & Szewzyk 2011), it is desirable to achieve a more steady and controlled flow, even if this implies a substantially lower shear rate (Verhaagen 2012;. Such acoustic streaming flow induced by an oscillating bubble has been also used to propel microparticles (Bertin et al 2015) or even milimetric objects (Dijkink et al 2006).…”
Section: R Bolaños-jiménez and Othersmentioning
confidence: 99%
“…As the bubble diameter scales down to the 10-to 30-μm range, the cylindrical cavity geometry would require advanced hydrophobic treatment to hold a microbubble stable due to the increased surface tension forces (19). Therefore, advanced threedimensional (3D) microfabrication techniques could be used to create spherical voids inside the swimmer's body to increase the stability of a trapped air bubble (23). Previously, Louf et al (13) demonstrated a hovering microswimmer by trapping a microbubble underneath its body, facing toward the substrate.…”
mentioning
confidence: 99%
“…Moreover, their cylindrical cavity design required hydrophobic surface modification to stabilize the bubble during acoustic actuation. In general, the locomotion behavior of bubble-based microrobots in a low-Reynolds flow regime is complex, especially when the microbubble is below the 30-μm range and oscillates near solid walls, due to the nonlinear acoustic forces (23). The interaction of such acoustically powered microrobots near walls has not been fully investigated yet and therefore their directionality control remains a challenge.…”
mentioning
confidence: 99%
“…While applied here to autophoretic propulsion, this method of control via selective shape transformation is in fact broadly applicable to other means of propulsion, which may be preferable for biomedical applications. For instance, if the catalytic end-caps were to be replaced by encapsulated bubbles driven by ultrasound [11], this swimmer would drive very similar flows to the phoretic swimmer in all three configurations, with the additional benefit of biocompatibility [39].…”
Section: Discussionmentioning
confidence: 99%